Preparation and properties of polyaniline/viscose fiber adducts. Issue 4 (16th June 2015) - Li, Guodong; Yu, zhuo; Han, Na; Zhang, Xingxiang; Wang, Ning; Qi, Xiaoling
Abstract : Polyaniline (PANI)/viscose fiber (VF) adducts were prepared by the polymerization of aniline with ammonium persulfate as an oxidant and VF as a template in hydrochloride solution. PANI deposited on the surface of VF because of the interaction between PANI and VF. The effect of PANI content and the reaction time on the performance of PANI/VF adducts were evaluated, respectively. The electrical conductivity of PANI/VF adducts increased with reaction time from 2 to 8 h, but the conductivity decreased at the higher reaction time because of the aggregation of PANI particles. With the increasing of reaction time, the tensile strength initially decreased to 1.299 cN/dtex at 3 h, subsequently increased to 1.528 cN/dtex at 8 h, and finally diminished a little to 1.475 cN/dtex at 24 h. When the adducts were washed in water, the conductivity only decreased from 2.71 × 10 −3 to 2.4 × 10 −3 S/cm, and it was stable after washing 50 times. POLYM. COMPOS., 38:782–788, 2017. © 2015 Society of Plastics Engineers